Educational Organizational Strategies at The Secondary School Level in Facing Global Challenges - Hadi, Alya Fatma; Fatimah Az-Zahra; Nadiya Salsabila (International Journal of Geography, Social, and Multicultural Education, 2023)
Educational organization strategy is the most important element in facing global challenges at the secondary school level. In an increasingly complex era of globalization, secondary schools are expected to be able to produce graduates who are competent and ready to face the demands of the rapidly changing world of work. This article was created to find out and analyze the strategies of educational organizations at the secondary school level in facing global challenges. This research uses a qualitative approach with a descriptive research method sourced from literature study. Literature study is a research method that uses review results from other journals as a reference source. From these results it is known that: (1) Educational organization must be implemented well in secondary schools in line with current developments. (2) It is important for education to be integrated with strategic management that ensures that educational goals and long-term vision are achieved. (3) Education as an organization also needs compact cooperation between society and government to build synergy between educational institutions